PEMBELAJARAN MENULIS TEKS PIDATO DAN BERPIDATO KELAS X DI SMA NEGERI 3 SUKOHARJO - Santosa, Jaka; Markhamah, Markhamah; Nasucha, Yakub (Universitas Muhammadiyah Surakarta, 2015)
This study has four aims, (1) the procedure of learning to write text to speech and speech in the classroom, (2) learning strategies and what the media writes text to speech and speech in the classroom, (3) student activity in learning to write text to speech and speech in the classroom, and (4) learning outcomes writing text to speech and speech. This includes descriptive qualitative research which took place in SMA Negeri 3 Sukoharjo. Data in the form of words and actions. Sources of data obtained from sources, events,Â and documents. Informant is Indonesian teachers and students. Events are learning activities Indonesian X1 class 2nd semester of academic year 2012/2013. The document in question is a document relating to the teaching of writing. Data collection techniques were interviews, observation, and documentary. Research findings in the field, among others, (1) the learning procedure by submitting a text to speech material on speech. Then compose the theme is developed into a framework and final drafting speeches, (2) application of learning strategies to write text to speech and speech with the approach that has been programmed patterns , the approach of process skills and communicative approach, (3) students activate in learning writing text to speech and speech have been carried out by providing learning facilities and trust management using effective learning infrastructure, (4) learning to write text to speech and speech by using the approach of process skills and communicative approaches undertaken by teachers Indonesian subjects in SMA Negeri 3 Sukoharjo obtain following result, students who earn good grades for writing text to speech 80 % and 88 % speech practice, then students who received grades enough to write the speech 20 % and 3 % speech practice, and students who obtain less value to the writing of the speech is not there, to practice speech while there were 9 % .